Intégration politique des partis islamistes et processus de « spécialisation » : perspective comparée Tunisie-Maroc - Anca Munteanu (L’Année du Maghreb)
In Morocco, as in Tunisia, the political integration of the two main Islamist parties has given rise to a project of «specialisation» aimed at introducing a distinction between partisan activities and associative and preaching activities. Starting from the trajectories of the Ennahdha party and the Moroccan PJD, this article proposes to highlight the differences in the «specialization» processes initiated by the two parties. This transformation is analysed here as referring to a separation between political activists and preachers. It underlines the complex relations between the PJD and the MUR, as well as between the militants of Ennahdha and the associative field in the light of the «specialisation». It also identifies the phenomenon of movement of members of different organisations between the political domain and the sphere of social and religious action. The analysis shows that in the two studied cases the «specialisation» does not lead to an effective separation between partisan action and social and preaching activity and does not eliminate the porosity of the limits between politics and religion.